2020
DOI: 10.1371/journal.pone.0237097
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating modified diets and dietary supplement therapies for reducing muscle lipid accumulation and improving muscle function in neurofibromatosis type 1 (NF1)

Abstract: Neurofibromatosis type 1 (NF1) is a genetic disorder that affects a range of tissue systems, however the associated muscle weakness and fatigability can have a profound impact on quality of life. Prior studies using the limb-specific Nf1 knockout mouse (Nf1 Prx1-/-) revealed an accumulation of intramyocellular lipid (IMCL) that could be rescued by a diet supplemented with L-carnitine and enriched for medium-chain fatty acids (MCFAs). In this study we used the Nf1 Prx1-/mouse to model a range of dietary interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Weight, BMI, WC, HC and WHR were not correlated with these lesions. Nevertheless, interestingly, previous studies showed that NF1-associated neurofibromas present neoplastic Schwann cells with lipid droplets accumulation, express leptin and have higher chances of having intermingled adipocytes than non NF1-associated neurofibromas [24,[69][70][71]. Lipid droplets accumulation and overexpression of fatty acid synthesis (FASN) were also found in MPNSTs [25].…”
Section: Table 1 Comparison Of Head Circumference and Anthropometric ...mentioning
confidence: 98%
“…Weight, BMI, WC, HC and WHR were not correlated with these lesions. Nevertheless, interestingly, previous studies showed that NF1-associated neurofibromas present neoplastic Schwann cells with lipid droplets accumulation, express leptin and have higher chances of having intermingled adipocytes than non NF1-associated neurofibromas [24,[69][70][71]. Lipid droplets accumulation and overexpression of fatty acid synthesis (FASN) were also found in MPNSTs [25].…”
Section: Table 1 Comparison Of Head Circumference and Anthropometric ...mentioning
confidence: 98%
“…The Nf1 Prx1 -/- muscle phenotype could be rescued using a dietary intervention enriched for medium-chain fatty acids (MCFAs) and L-carnitine, showing a dramatic decrease in muscle lipid (71%) and a partial improvement in grip strength [ 12 ]. A subsequent 2020 study trialed several variations of this dietary intervention [ 13 ]. This included L-carnitine and MCFAs separately and in combination, an intermittent dosing regimen (5/7 days), a mitochondrial cocktail (L-carnitine, CoQ10, creatine and riboflavin), and a low-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…While the NF1 bone phenotype has been correlated with deficient osteogenesis [ 8 ], microarray analysis examining cortical bone samples from Nf1 Prx1 -/- and Nf1 Col1 -/- did show a disruption of lipid metabolism genes [ 9 ]. To investigate the potential role of diet and dietary rescue on bone, spine and long bone specimens were analyzed from our prior study comparing the impact of different dietary interventions on Nf1 Prx1 -/- mouse muscle [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest muscle weakness (Cornett et al, 2015; Stevenson et al, 2012) may be another under identified feature of NF1, that may be potentially treatable. Deficiencies in muscle function have been identified in NF1 patients, including decreased muscle size, muscle strength, and motor proficiency (Cornett et al, 2015; Stevenson et al, 2012; Vasiljevski et al, 2020). There is some evidence from mouse studies to suggest reduced muscle strength may be related to abnormal Ras or cAMP signaling (Sullivan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence from mouse studies to suggest reduced muscle strength may be related to abnormal Ras or cAMP signaling (Sullivan et al, 2014). Furthermore, murine studies have demonstrated accumulation of intramyocellular lipids that resolve with carnitine supplementation (Vasiljevski et al, 2020). Recently, treatment of a small cohort of children with L‐carnitine led to a significant improvement in muscle function including a 6‐min walk test, and dynamometry (Vasiljevski, 2020).…”
Section: Introductionmentioning
confidence: 99%